What determine firms' capital structure in China?. Issue 10 (7th October 2014) - Chen, Jian; Jiang, Chunxia; Lin, Yujia
Abstract : Purpose: – The purpose of this paper is to investigate the determinants of capital structure using a cross-section sample of 1, 481 non-financial firms listed on the Chinese stock exchanges in 2011. Design/methodology/approach: – Employing four leverage measures (total leverage and long-term leverage in terms of both book value and market value, respectively) this study examines the effects of factors with proven influences on capital structure in literature, along with industry effect and ownership effect. Findings: – The authors find that large firms favour debt financing while profitable firms rely more on internal capital accumulation. Intangibility and business risk increase the level of debt financing but tax has little impact on capital structure. The authors also observe strong industrial effect and ownership effect. Real estate firms borrow considerably more and firms from utility and manufacturing industries use more long-term debt despite compared with commercial firms. On the other hand, firms with state ownership tend to borrow more, while firms with foreign ownership choose more equity financing. Research limitations/implications: – The study uses cross-section data to avoid any potential time effects, which allows the authors to focus on their main research question – to identify the determinants of capital structure for Chinese firms. Future research may gain more insights using panel data and considering other factors such as crisis and financial reforms. Practical implications: – These results may provide important implications to investors in making investment decision and to firms in making financing decisions. Originality/value: – This paper uses by far the largest and latest cross-section sample from the Chinese stock markets, offering a more complete picture of the financing behaviours in the Chinese firms, with known characters and the impact of ownerships.